Malaysia My Second Home (MM2H) programme: the impact of perceived value on expressed intentions / Toh Poh See … [et al.] - Toh, Poh See; Aminudin, Norliza; A. Jamal, Salamiah; Adanan, Akmal (2011)
The government has initiated, organised and will continuously seek to improve the MM2H programme. The success in getting the wealthy foreigners will be meaningless if they are not satisfied with their stay in Malaysia. Since long-term tourism depends a lot on word-of-mouth, their recommendation will be a promotion tool for the programme, thus ensuring their satisfaction is vital Research on the second homers' perception towards the country is very much lacking thus this study aims to fulfil the gap. The main objective of this research is to undertake a qualitative approach on the perceptions on Malaysia by the second homers who stay here under the MM2H programme. Looking at the significance of the economic contribution of the second homer under the MM2H programme, the information obtained from this research could assist both the government and private sector in fulfilling the needs and wants of the foreigners, which in turn lead to their satisfaction level. Satisfied customers will usually have positive word of mouth; this in turn will generate more foreigners to the programme (MM2H). Academically this research will add value to the literature of second homes especially for host country from this side of the world. Nationally, the country will gain in terms of foreign exchange for the national economy.